Tinjauan Yuridis Terhadap Netralitas Pegawai Negeri Sipil dalam Pemilihan Kepala Daerah Menurut Undang-Undang No. 5 Tahun 2014 Tentang Aparatur Sipil Negara - Micael Josviranto (Jurnal Ilmiah Wahana Pendidikan, 2021)
The Regional Election Committee is directly mandated by Law No.23 of 2014 concerning Regional Government which is also the hope of the local community and is also one of the objectives of regional autonomy, but there is a negative impact felt by the State civil apparatus to be co-opted and become a subordination of political forces incumbent) who are candidates for regional head elections, this cannot be denied because the State civil apparatus can be a significant political machine to win the Regional Election, The partisanship of civil servants into practical politics is not not due to the fact that even though the merit system in each of the positions of state civil apparatus at all levels both at the central and regional levels must be based on competence. Based on Law No. 5 of 2014 concerning the State Civil Apparatus, but in the system still gives full authority to the elected regional head in placing a person of the State civil apparatus to occupy certain positions of office.